2010
DOI: 10.1590/s0074-02762010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of macromolecules by cercariae during skin penetration and transformation to schistosomula (Schistosoma mansoni)

Abstract: Here, we observed the uptake of membrane-impermeant molecules by cercariae as they penetrate the skin and are transformed into schistosomula. We propose that membrane-impermeant molecules, Lucifer yellow, Propidium iodide and Hoechst 33258 enter the parasite through both thenephridiopore and the surface membrane and then diffuse throughout the body of the parasite. We present a hypothesis that the internal cells of the body of the schistosomulum represent a new host-parasite interface, at which skin-derived gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…2007), sporocyst (Mattos et al . 2006), and cercariae (Thornhill et al 2009). The probe Hoechst 33258, which binds DNA of cells, is a very sensitive indicator of membrane integrity, since even the worms of the LE and LE-PZQ isolates – not exposed to PZQ in vitro or in vivo – showed slight labelling with the probe, leading to some variability among the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2007), sporocyst (Mattos et al . 2006), and cercariae (Thornhill et al 2009). The probe Hoechst 33258, which binds DNA of cells, is a very sensitive indicator of membrane integrity, since even the worms of the LE and LE-PZQ isolates – not exposed to PZQ in vitro or in vivo – showed slight labelling with the probe, leading to some variability among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitive tool for identification of tegumental lesions in S. mansoni is the fluorescent probe Hoechst 33258 (Oliveira et al 2006). This probe has already been used in various studies, not only in adult worms (Lima et al 1994;Oliveira et al 2006), but also in schistosomula (Kusel et al 2007), sporocyst (Mattos et al 2006), and cercariae (Thornhill et al 2009). The probe Hoechst 33258, which binds DNA of cells, is a very sensitive indicator of membrane integrity, since even the worms of the LE and LE-PZQ isolatesnot exposed to PZQ in vitro or in vivoshowed slight labelling with the probe, leading to some variability among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…In newly transformed schistosomula, the ability to modify the surface membrane through acquisition of host molecules represents the formation of a host-parasite interface, at which skin-derived factors may stimulate internal membrane receptors to drive important actions of parasite development and facilitate escape from the host immune system [26, 27, 28, 29, 30]. In the present study, a considerable number of the genes up-regulated after 12 hours of stimulus by portal serum were related to membrane activity, mainly regarding the transport of substances, both on the cell membrane as well as in internal organelles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in vitrotransformed cercariae cultured for 3 days have been widely used for experimental approaches (Chai et al 2006). However, Thornhill et al (2010) reported that artificially transformed schistosomula were different from host-derived ones in their ability to take up macromolecules. The authors hypothesized that a specific stimulus from the host during skin penetration was lacking in schistosomula generated in vitro.…”
Section: Introductionmentioning
confidence: 99%